Altered Spatial Organization of Dynamic Functional Network Associates With Deficient Sensory and Perceptual Network in Schizophrenia - He, Hui; Luo, Cheng; He, Chuan; He, Manxi; Du, Jing; Biswal, Bharat B.; Yao, Dezhong; Yao, Gang; Duan, Mingjun (Frontiers in Psychiatry, 2021)
Schizophrenia is currently thought as a disorder with dysfunctional communication within and between sensory and cognitive processes. It has been hypothesized that these deficits mediate heterogeneous and comprehensive schizophrenia symptomatology. In this study, we investigated as to how the abnormal dynamic functional architecture of sensory and cognitive networks may contribute to these symptoms in schizophrenia. We calculated a sliding-window based dynamic functional connectivity strength (FCS) and amplitude of low frequency fluctuations (ALFF) maps. Then, using group independent component analysis, we characterized spatial organization of dynamic functional network (sDFN) across various time windows. The spatial architectures of FCS/ALFF-sDFN were similar with traditional resting-state functional networks, and can not be accounted by length of the sliding window. Moreover, schizophrenic subjects demonstrated reduced dynamic functional connectivity (dFC) within sensory and perceptual sDFNs, as well as decreased connectivity between these sDFNs and high-order frontal-sDFNs. The severity of patients' positive and total symptoms were related to these abnormal dFCs. The results revealed that the sDFN during rest might form the intrinsic functional architecture, and functional changes associated with psychotic symptom deficit. Our results support the hypothesis that dynamic functional network may influence the aberrant sensory and cognitive function in schizophrenia, further highlight that targeting perceptual deficits could extend our understanding of schizophrenia’s pathophysiology.